Voice interaction design crafting the new conversational speech systems - Harris, Randy Allen. (Morgan Kaufmann series in interactive technologies., 2005)
From the voice on the phone, to the voice on the computer, to the voice from the toaster, speech user interfaces are coming into the mainstream and are here to stay forever. Soundly anchored in HCI, cognitive psychology, linguistics, and social psychology, this supremely practical book is loaded with examples, how-to advice, and design templates. Drawing widely on decades of researchin lexicography, conversation analysis, computational linguistics, and social psychologyauthor Randy Allen Harris outlines the principles of how people use language interactively, and illustrates every aspect of design work. In the first part of the book, Harris provides a thorough conceptual basis of language in all its relevant aspects, from speech sounds to conversational principles. The second part takes you patiently through the entire process of designing an interactive speech system: from team building to user profiles, to agent design, scripting, and evaluation. This book provides interaction designers with the knowledge and strategies to craft language-based applications the way users will expect them to behave. *Loaded with examples and practical synopses of the best practice. *An ideal combination of conceptual base, practical illustrations, and "how-to" advicefor design and for the entire design process. *Will bring novice voice designers fully up to speed, and give experienced designers a new understanding of the principles underlying human speech interaction, principles from which to improve voice interaction design.